Retroperitoneal Nephrometry Scoring System (RETRO) for Minimal-Invasive Partial Nephrectomy - Ye, Sunyi; Zhu, Lixian; Wang, Ping; Sun, Xinxing; Xu, Xin; Zhao, Feng; Yao, Xiaolin; Huang, Qiang; Dai, Yun; Xia, Dan; et al. (Urology Journal, 2023)
Purpose: To propose a standardized scoring system of renal tumors suitable for partial nephrectomy based on mini-invasiveness and retroperitoneal approach. Materials and Methods: One-hundred and five patients in retroperitoneal group were prospectively enrolled from January 2017 to December 2018. Perioperative characteristics of all patients were collected: age, gender, BMI, preoperative blood test and imaging results, operation time (the time period starts from the skin incision to the final skin closure), estimated blood lost, clamping time, complications within 30 days, American Society of Anesthesiologists (ASA) score, pathology. An algorithm was extracted, and it was used to predict the risk of complications. Results: Symptoms, ASA score and RETRO score were significantly correlated to postoperative complications, excluding tumor size, ischemia time and operation time. Adjusted RETRO points were an independent factor to predict complication rate (p = 0.006). Limitation was that it did not analyze the relationship between the RETRO score and the long-term outcomes. Conclusion: The RETRO score simplifies the risk evaluation of partial nephrectomy for patients with renal tumor, especially benefits those surgeries performed under robot-assisted laparoscope via retroperitoneal approach. The new RETRO score system that we developed is a selection criterion to perform surgery via different approaches, and an accurate system to evaluate the complexity during partial nephrectomy.